THEORETICAL APPROACH TO FORMATION OF SYSTEM OF MANAGEMENT ACCOUNTING - E. Sedova (Publishing House of the State University of Management, 2016)
In the article theoretical approach to formation of system of management accounting is considered, the main objective of management accounting is revealed. The modern directions of management accounting are considered: the management strategic accounting, calculation of expenses of full life cycle, target calculation, calculations in system of continuous improvement.